ANTIMICROBIAL EFFECTS OF POLYPHENOLS FROM FERMENTED AND NON-FERMENTED APPLE AND CARROT POMACE AGAINST ESCHERICHIA COLI - Anghel, Andrei (Food and Feed Research, 2024)
The pig farming industry faces significant challenges during the weaning period, often resulting in reduced growth rates and higher mortality among piglets. Traditionally, antibiotics and zinc oxide have been used to manage these issues. However, concerns about antibiotic resistance and environmental pollution have led to strict European regulations limiting or banning their use. This fact has created an urgent need for alternative solutions, with polyphenols emerging as promising candidates due to their bioactive properties, including anti-inflammatory, antioxidant, and antimicrobial effects. These properties are particularly important for preventing weaning-related problems, which are frequently caused by the Escherichia coli F4 (K88) bacterium. The present study focused on evaluating the antimicrobial properties of polyphenols extracted from apple pomace and carrot pomace, both in their unfermented form and after fermentation with Saccharomyces cerevisiae. The antimicrobial activity was assessed in vitro by monitoring bacterial growth through absorbance measurements at different intervals over 24 hours, at 37°C. The results indicated that polyphenols possess significant antimicrobial effects in both their unfermented and fermented states. The polyphenol extract from apple pomace inhibited E. coli growth at a minimum concentration of 5.6 µg (GAE)/ml, while the extract from fermented apple pomace had a higher minimum inhibitory concentration of 50 µg (GAE)/ml. For carrot pomace, only the concentration of 151 µg (GAE)/ml showed an inhibitory effect on E. coli growth, whereas the polyphenol extract from fermented carrot pomace significantly reduced bacterial growth at a concentration of 303 µg (GAE)/ml. The extent of bacterial inhibition was influenced by the concentration of polyphenols and the specific types of polyphenols present in the extract. Notably, despite having a lower overall concentration, the fermented polyphenol extracts achieved similar levels of bacterial growth inhibition as the unfermented extracts at higher concentrations. These findings highlight the potential of agro-industrial by-products such as apple and carrot pomace to provide bioactive compounds that could serve as effective alternatives to antibiotics and zinc oxide in livestock farming. By exploiting these natural resources, the industry might move towards more sustainable and environmentally friendly practices while still effectively managing the challenges associated with weaning piglets.